Guideline for developing a water pollution prevention and control plan for the Akaki Catchment, Ethiopia - Kibret, M.; Haile, Alemseged Tamiru; Gebre, E. S.; Terfie, T. A.; Hiruy, A. M.; Yibel, B.; Mateo-Sagasta, Javier (International Water Management Institute, 2025)
This guideline provides a comprehensive planning framework for preventing and controlling water pollution in Ethiopia, with the Akaki Catchment as a case study. Water pollution is a growing national concern that threatens public health, reduces agricultural productivity, damages ecosystems, and creates heavy economic costs. In Ethiopia, it contributes to thousands of deaths annually, accelerates biodiversity loss and increases the burden of water treatment.